Malnutrition and infection lead to poor prognosis and heavy financial burden of patients with chronic heart failure - Jia, Xu; Yu, Xing-long; Lu, Bin; Shang, Yuan-yuan; Shen, Long-fei; Li, Yu-lin; Zhang, Wei; Zhong, Ming; Han, Lu; Wang, Zhi-Hao (Frontiers in Cardiovascular Medicine, 2022)
Background Chronic heart failure (CHF) is a major public health concern, as it is associated with poor prognosis and heavy financial burden. In recent years, there has been increasing interest in medications for CHF in China, but few studies pay attention to the effects of nutrition and infection. Methods and results This was a retrospective study collected patients with CHF admitted to the Department of Cardiology of Qilu Hospital of Shandong University from January 2017 to May 2018. Patients were classified according to the prognosis and the financial burden. Through comparison and regression analysis, we found that the factor associated with worse prognosis were decreased heart rate, albumin and prealbumin; β-blockers and mineralocorticoid receptor antagonism (MRA) were the factor improved the prognosis of patients with CHF; the factor overburdening financial condition were infection, decreased prealbumin, high Alanine aminotransferase (ALT), usage of recombinant human brain natriuretic peptide (rhBNP) and Levosimendan; aspirin and Sacubitril/Valsartan were the factor releasing financial burden of patients with CHF. Then, we grouped by Controlling Nutritional Status (CONUT) score, which enabled evaluation of the patient's protein reserve and immune defenses. Patients in the malnutrition group had higher infection ratios, longer hospital stays, and greater hospital expenses than the normal group. The improvement ratios of therapeutic outcomes in the moderate or severe malnutrition group were lower than in the normal and mild malnutrition group. Conclusion Malnutrition and infection caused poor prognosis and increased financial burden of patients with CHF. The high CONUT score indicated the CHF patient's unfavorable prognosis and heavy financial burden.